State of Illinois - Common Spatial Geodatabase for the Social Sciences - Lotspeich-Yadao, Michael (University of Illinois at Urbana-Champaign, 2021)
This geodatabase serves two purposes: 1) to provide State of Illinois agencies with a fast resource for the preparation of maps and figures that require the use of shape or line files from federal agencies, the State of Illinois, or the City of Chicago, and 2) as a start for social scientists interested in exploring how geographic information systems (whether this is data visualization or geographically weighted regression) can bring new meaning to the interpretation of their data. All layer files included are relevant to the State of Illinois. Sources for this geodatabase include the U.S. Census Bureau, U.S. Geological Survey, City of Chicago, Chicago Public Schools, Chicago Transit Authority, Regional Transportation Authority, and Bureau of Transportation Statistics.
Keywords: State of Illinois; City of Chicago; Chicago Public Schools; GIS; Statistical tabulation areas; hydrography